A rare mutation in alkaptonuria patient - Agarwal, Ansh; Goyal, Kashish; Mathur, Priyanshu; Minocha, Priyanka; Bansal, Kanika; Mathur, Nitish (Indian Journal of Child Health, 2020)
Alkaptonuria is a rare autosomal recessive metabolic disorder due to mutation in enzyme homogentisate 1,2-dioxygenase resulting in accumulation of homogentisic acid. The homogentisate 1,2-dioxygenase (HGD) gene has been mapped to chromosome 3q21- q23 and comprises 14 exons. A wide variety of causative mutations has been reported. Here, we are presenting a case report of a 2-year-old male child with a history of dark black-brown spots of urine on diaper with c.674G>C (p.Arg225Pro) mutation at exon 10 of HGD gene. The observed variant had a minor allele frequency of 0.0200% and 0.0004% in 1000 genomes and gnomAD database, respectively.